2012
DOI: 10.1080/15374416.2012.660690
|View full text |Cite
|
Sign up to set email alerts
|

The Parent–Child Relationship as Predictor of Eating Pathology and Weight Gain in Preadolescents

Abstract: The present study examined the role of attachment toward mother and father as a predictor of eating pathology and weight gain among preadolescent boys and girls. Self-report questionnaires and adjusted body mass index (BMI) were administered from a community sample of 601 preadolescents (8-11 years; 48% female) at baseline and once again 1 year later. Significant baseline associations were found between attachment toward both parents and several features of eating pathology. No baseline correlations were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 66 publications
13
72
1
8
Order By: Relevance
“…Mothereinfant relationship problems have been associated with feeding difficulties in early childhood [28,29] and previous research has shown that insecure attachment to the mother significantly increases the risk of restrained eating over a 1-year period during preadolescence [30]. Contrary to our hypothesis, we did not find motherechild relationship problems measured during infancy to be predictive of eating behavior problems in preadolescence.…”
Section: Discussioncontrasting
confidence: 83%
“…Mothereinfant relationship problems have been associated with feeding difficulties in early childhood [28,29] and previous research has shown that insecure attachment to the mother significantly increases the risk of restrained eating over a 1-year period during preadolescence [30]. Contrary to our hypothesis, we did not find motherechild relationship problems measured during infancy to be predictive of eating behavior problems in preadolescence.…”
Section: Discussioncontrasting
confidence: 83%
“…Groh et al 2012), depression (Brumariu and Kerns 2010), and externalizing behaviour problems (Fearon et al 2010). Many separate studies support this effect for a list of other problems such as dissociation (Liotti 2006), eating pathology (Goossens et al 2012), non-suicidal self-injury (Bureau et al 2010), or even the symptomatology and course of schizophrenia (Ponizovsky et al 2007). As a consequence, insecure attachment is considered an important transdiagnostic risk factor in the development of psychopathology and could therefore be an important factor to take into account during the treatment of any child and adolescent emotional or behavioural disorder.…”
Section: Attachment Theorymentioning
confidence: 91%
“…For example, some studies indicate an association between insecure maternal attachment and being overweight [16, 17] with anxious attachment being specifically linked with BMI possibly through the tendency to engage in disinhibited eating [18]. Similarly, Rommel et al [19] identified an association between parental attachment and emotional awareness in obese patients, and Holland, Dallos and Olver [20] concluded from their qualitative study that complex, conflicted family relationships influence attachment styles which in turn lead to a reliance on food as a coping mechanism.…”
Section: Introductionmentioning
confidence: 99%